PENGARUH KEWAJARAN HARGA DAN NILAI PELANGGAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN SKINCARE SKINTIFIC DI KOTA BATAM - Nainggolan, Nora Pitri; Purba, Tiurniari (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2025)
This study aims to test the fairness of price and customer value on consumer purchasing decisions at Skintific Skincare in Batam City. This study uses an associative method with a quantitative research type. The research sample consisted of 100 respondents who were people who had purchased and used Skintific Skincare in Batam City. The data collection method used was primary data. Based on the data and analysis that has been done, this study shows that price fairness has a positive and significant effect on consumer purchasing decisions at Skintific Skincare in Batam City. The customer value variable has a positive and significant effect on consumer purchasing decisions at Skintific Skincare in Batam City. And simultaneously, price fairness and customer value have a positive and significant effect on consumer purchasing decisions at Skintific Skincare in Batam City.